Pengaruh Kompensasi, dan Motivasi Kerja Terhadap Kinerja Karyawan Perusahaan Ekspedisi - Putri Maimunah Selandra; Resista Vikaliana (Journal of Trends Economics and Accounting Research, 2023)
This study was conducted to analyze the effect of compensation and work motivation on employee performance at PT. SiCepat Express South Bekasi branch. In this study, the researcher distributed questionnaires to 40 employees of PT SiCepat Express, South Bekasi branch. The method used in this study was a quantitative method with the type of research method correlational. According to Arikunto, (2014: 247- 248), correlational studies are research that is intended to determine whether there is a relationship between two or several variables. This study used quantitative methods with data analysis techniques of multiple linear regression analysis because the independent variables used were more than one. The variables in this study included Compensation (X1) and Work Motivation (X2) as the independent variables and Employee Performance (Y) as the dependent variable. The data analysis techniques used were validity test, reliability test, descriptive analysis, classical assumption test, multiple regression analysis, and hypothesis testing. The data and analysis of this study were processed using the SPSS version 25 program. Based on the results of the analysis carried out, it can be interpreted that compensation had a positive and significant effect on employee performance at PT. SiCepat Express, South Bekasi Branch. This is evidenced by the percentage of the effect of compensation and work motivation on employee performance as obtained from the results of the correlation coefficient test by 83.3%. The variable compensation and work motivation explained the variations in employee performance by 67.7% and the rest was explained by factors or other variables outside of the model.